2005
DOI: 10.1381/0960892053923716
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Adjustable Gastric Banding: Weight Loss, Co-morbidities, Medication Usage and Quality of Life at One Year

Abstract: At 1 year after LAGB, patients had experienced significant weight loss, resolution of comorbidities, decreases in medication usage, and improvements in QoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(72 citation statements)
references
References 15 publications
5
65
0
2
Order By: Relevance
“…Most research shows an improvement in Type 2 diabetes 22,23 (79%-81%), metabolic syndrome (78%) hypertension (67%), dyslipidemia (66%), reflux (66%), asthma (57%), arthritis/joint pain (70%), polycystic ovary syndrome (48%), and depression (57%). [23][24][25] Unlike the metabolic effects seen with bypass procedures such as gastric bypass and duodenal switch, the remission or improvement in conditions such as Type 2 diabetes and metabolic syndrome after AGB is believed to be because of the direct effects of weight loss. Therefore, the time required to see improvement in these conditions can vary substantially, and is dependent on the amount of weight loss.…”
Section: Resolution Of Comorbid Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most research shows an improvement in Type 2 diabetes 22,23 (79%-81%), metabolic syndrome (78%) hypertension (67%), dyslipidemia (66%), reflux (66%), asthma (57%), arthritis/joint pain (70%), polycystic ovary syndrome (48%), and depression (57%). [23][24][25] Unlike the metabolic effects seen with bypass procedures such as gastric bypass and duodenal switch, the remission or improvement in conditions such as Type 2 diabetes and metabolic syndrome after AGB is believed to be because of the direct effects of weight loss. Therefore, the time required to see improvement in these conditions can vary substantially, and is dependent on the amount of weight loss.…”
Section: Resolution Of Comorbid Conditionsmentioning
confidence: 99%
“…[23][24][25] Nonetheless, there is no consensus on QoL tools that should be used, nor if the results are lasting. There definitely seems to be a "honeymoon" phase of improvement in QoL for patients, but there seems to be a drift downward in their scores after this.…”
Section: Changes In Quality Of Lifementioning
confidence: 99%
“…Furthermore, the existing literature is primarily quantitative in nature, using validated measures to determine changes such as quality of life [24,25], eating behaviour [26,27], improvement in comorbidities [16,28], and long-term weight loss [10]. Complications following surgery such band slippage, oesophageal dilatation and pouch dilatation have also been explored [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…A recently published retrospective analysis of 2,090 banding patients found a mean EWL of 52.9 percent at 5 years postoperatively. However, a review of individual studies show more inconsistent outcomes, with percentages of EWL ranging from less than 30 percent to as much as 70 percent [3]. Two recently published studies found the majority of patients failed to achieve the benchmark of 50 percent of EWL at 2 and 3 years postoperatively [4].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have reported improved quality of life (QOL) after gastric banding surgery [3,[5][6][7][8]. A study by Freys et al [9] reported a significant improvement in QOL in 73 banding patients but reported a high number of complications (38%) that resulted in reoperation.…”
Section: Introductionmentioning
confidence: 99%